2019
DOI: 10.1101/2019.12.17.878363
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modular prophage interactions driven by capsule serotype select for capsule loss under phage predation

Abstract: Klebsiella species are able to colonize a wide range of environments and include worrisome nosocomial pathogens. Here, we sought to determine the abundance and infectivity of prophages of Klebsiella to understand how the interactions between induced prophages and bacteria affect population dynamics and evolution. We identified many prophages in the species, placing these taxa among the top 5% of the most polylysogenic bacteria. We selected 35 representative strains of the Klebsiella pneumoniae species complex … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 105 publications
2
39
0
Order By: Relevance
“…This fits our previous studies on the infection networks of Kpn prophages 26 and suggests that a population of cells encoding and expressing a given serotype has more frequent phage-mediated genetic exchanges with bacteria of identical or similar serotypes ( Figure 6A). In this context, phages carrying multiple capsule depolymerases have broader host range and may have a key role in phagemediated gene flow between very distinct serotypes.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This fits our previous studies on the infection networks of Kpn prophages 26 and suggests that a population of cells encoding and expressing a given serotype has more frequent phage-mediated genetic exchanges with bacteria of identical or similar serotypes ( Figure 6A). In this context, phages carrying multiple capsule depolymerases have broader host range and may have a key role in phagemediated gene flow between very distinct serotypes.…”
Section: Discussionsupporting
confidence: 91%
“…for the transfer of temperate phages from one bacterial genome to another. We found that 97% of the strains were lysogens, with 86% being poly-lysogens, in line with our previous results in a much smaller dataset 26 .…”
Section: Gene Flow Is Higher Within Than Between Serotype Groupssupporting
confidence: 92%
See 2 more Smart Citations
“…Capsule extraction and quantification. The bacterial capsule was extracted as described in (Domenico et al 1989) and quantified by using the uronic acid method (Blumenkrantz and Asboe-Hansen 1973). Briefly, 500 μL of an overnight culture was mixed with 100 μL of 1%…”
Section: Generation Ofmentioning
confidence: 99%